Efektivitas Ekstrak Etanol Biji Pinang Terhadap Densitas GLUT4 pada Sel-Sel Otot Rangka Mencit yang Terinduksi Hiperglikemia - MULIA SAFRIDA SARI; AHMAD RIDWAN (Departemen Biologi, Institut Pertanian Bogor, 2016)
Betel nut (Areca catechu) was proven to have antihyperglycemic activity through increased PI3K pathway in the GLUT4 translocation in cells. However, research on the ethanol extract of betel nut in Indonesia is still limited. The main problem in this study was whether the ethanol extract of betel nut could improve glucose tolerance in a two-hour postprandial period and whether the ethanol extract of betel nut could induce GLUT4 translocation in skeletal muscle cells of mice induced hyperglycemia. Glucose tolerance test results showed that treatment of the ethanol extract of betel nut for 24 days with all doses tested: P50,100,150,200 and 250 mg/kg body weight could improve glucose tolerance in a two-hour postprandial period. The protein electrophoresis of that fasting and one hour postprandial state treatments resulted an increase in GLUT4/βActin density ratio of P250 group compared to negative and positive controls. In this case, GLUT4/βActin density ratio of P100,P200 and P250 were higher than that GLUT4/βActin density ratio of P50 and P150. Increased in GLUT4/βActin density ratio showed enhancement of the GLUT4 in skeletal muscle cells in fasting and one hour postprandial state after treated with ethanol extract of betel nut.